ANALYSIS OF RS34637584 POLYMORPHISM IN THE LRRS2 GENE IN PATIENTS WITH PARKINSON’S DISEASE - Kotlica, Boba; Ristanović, Momčilo; Novaković , Ivana (Medicinski podmladak, 2022)
Introduction: Parkinson’s disease (PD) belongs to neurodegenerative diseases, and with a prevalence of 1% to 2% in persons older than 65 years and over 4% in persons older than 85 years is the second most common in this group of diseases. The basis of PD is the death of dopaminergic neurons in the CNS, primarily in the basal ganglia and the substance nigra. The LRRK2 / PARK8 gene is located on the short arm of chromosome 12. This gene contains various variants associated with PD, of which the most common mutation is c.6055G> A (p.Gly2019Ser), also referred to as rs34637584. The aim of this study was to determine the frequency of the c.6055G> A (rs34637584) mutation in the LRRK2 gene in a group of patients with PD from Serbia. Material and methods: The study included a group of 127 patients with PD from tertiary institutions in Serbia, as well as an appropriate control group without neurological diseases. Molecular genetic analysis was performed by real-time PCR, using a commercial TaqMan assay. Results: Mutation c.6055G> A ie. rs34637584 variant was detected in 1 of 127 examinees with PD (0.7%). That patient was without a previous family history of PD. This mutation was not found in the control group. Conclusion: The results obtained match with literature data for the European, especially southern European population. Testing of LRRK2 mutation c.6055G> A (rs34637584) should be part of the PD test protocol. Keywords: LRRK2, rs34637584, Parkinson’s disease, real-time PCR